Modular Hydrogel−Mesoporous Silica Nanoparticle Constructs for Therapy and Diagnostics. Issue 3 (19th December 2021) - Gerstenberg, Melanie; Stürzel, Christina M.; Weil, Tanja; Kirchhoff, Frank; Lindén, Mika
Abstract : Self‐assembled peptide fibrils are abundant in in vivo systems and have been associated both with normal physiological functions and with different diseases. Herein, a proof‐of‐concept study is presented, where aggregates of synthetic, fibril‐forming peptides are studied as carriers for mesoporous silica nanoparticles (MSNs), giving a hydrogel@MSN hybrid structure. It is shown that when the peptide carries a cellular‐targeting motif, in this case arg‐gly‐asp (RGD), the fibrillar aggregates efficiently attach to cancer cells, and the attached MSNs can then be locally taken up by the cells and intracellularly release their cargo or release their cargo close to the outer membrane of the cells. If the targeting motif is not present on the fibrils, hardly any attachment of the fibrillar aggregates to the target cells occurs. The higher drug carrying capacity of the MSNs together with the efficient cellular attachment of the fibrillar aggregates represents a synergistic approach toward reaching a modular drug release system, bringing together the strengths of each component of the system. Finally, it is noted that although the experimental design is such that the fibrillar aggregates would not be capable of entering cells due to their large size, the approach would also be applicable to smaller fibrillar aggregates. Abstract : Self‐assembled peptide fibrils covalently functionalized with the cell adhesion‐enhancing peptide RGD are shown to efficiently attach to cancer cells. Furthermore, these fibrillar aggregates can be formulated together with mesoporous silica nanoparticles either during fibril formation or postformation, which enables extracellular drug release in close vicinity to the outer cell membrane.